The Association Between Vestibular Physical Examination, Vertigo Questionnaires, and the Electronystagmography in Patients With Vestibular Symptoms: A Prospective Study. (April 2017) - Gofrit, Shany G.; Mayler, Yulia; Eliashar, Ron; Bdolah-Abram, Tali; Ilan, Ophir; Gross, Menachem
Objects: Dizziness makes up a diagnostic and treatment challenge. The diagnostic accuracy of the medical history and vestibular physical examination in cases of vestibular symptoms is not clear. The aim of this study is to determine the association between vestibular physical examination, vestibular questionnaires, and electronystagmography (ENG) test in patients with vestibular symptoms. Methods: This is a prospective study of 135 adults with vestibular symptoms. The subjects underwent targeted physical examination and filled vestibular questionnaires, including the Dizziness Handicap Inventory (DHI), before ENG testing. The results of the physical examination and questionnaires were compared with the final ENG findings. Results: Of patients who had normal ENG results, 32.1% (17/52) showed abnormal physical examination, and 48.8% (40/82) of the patient who had normal physical examination showed abnormal ENG results ( P = .46). Among patients with severe disability by DHI, 46.4% (13/28) had an abnormal ENG, and 42.9% (12/28) had a normal ENG ( P = .39). Conclusions: This study did not demonstrate association between vestibular physical examination, vestibular questionnaires, and ENG results. Although history (augmented by questionnaires) and physical examination are the initial steps in the evaluation of vertigo, the current study suggests that they should be complemented by objective testing for evaluation of inner ear origin of vertigo.